2017
DOI: 10.1111/ejn.13585
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule stabilization promoted axonal regeneration and functional recovery after spinal root avulsion

Abstract: A spinal root avulsion injury disconnects spinal roots with the spinal cord. The rampant motoneuron death, inhibitory CNS/PNS transitional zone (TZ) for axonal regrowth and limited regeneration speed together lead to motor dysfunction. Microtubules rearrange to assemble a new growth cone and disorganized microtubules underline regeneration failure. It has been shown that microtubule-stabilizing drug, Epothilone B, enhanced axonal regeneration and attenuated fibrotic scaring after spinal cord injury. Here, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Our in-depth evaluation of the mechanism of action of DTX in axonal regeneration demonstrated that DTX regulated the dynamic rearrangement and stabilization of microtubules, which are essential for axonal outgrowth 60 , 61 , by improving the expression of Ace-tubulin and increasing the A/T ratio. DTX also strengthened and improved the motility of the growth cone, as revealed by the increasing intensity of F-actin staining, and thus elongated the microtubules by regulating the forces imposed on the microtubules by molecular motor proteins 47 , 62 , 63 . DTX further disentangled the coupled interaction of microtubules and F-actin, which facilitated further polymerization and stabilization of the overall cytoskeleton structure in the growth cone and filopodial extensions.…”
Section: Discussionmentioning
confidence: 89%
“…Our in-depth evaluation of the mechanism of action of DTX in axonal regeneration demonstrated that DTX regulated the dynamic rearrangement and stabilization of microtubules, which are essential for axonal outgrowth 60 , 61 , by improving the expression of Ace-tubulin and increasing the A/T ratio. DTX also strengthened and improved the motility of the growth cone, as revealed by the increasing intensity of F-actin staining, and thus elongated the microtubules by regulating the forces imposed on the microtubules by molecular motor proteins 47 , 62 , 63 . DTX further disentangled the coupled interaction of microtubules and F-actin, which facilitated further polymerization and stabilization of the overall cytoskeleton structure in the growth cone and filopodial extensions.…”
Section: Discussionmentioning
confidence: 89%
“…Pharmacological targeting of microtubules has become a popular and attractive approach to increase microtubule stability and integrity in various neurodegenerative disorders, such as Alzheimer's disease, Parkinson's disease, tauopathies and schizophrenia , including ALS . Administration of low doses of antimitotic compounds that target microtubules can improve pathology and outcomes in various disease models . These doses are generally 30ā€fold lower than those used in cancer therapy, where high doses of antimitotic compounds prevent cellular proliferation and promote cellular apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilizing microtubules could thus be a common approach to heal microtubule disturbances occurring in these various conditions, but the question arises as to what to use for this purpose. The most intensely studied microtubuleā€stabilizing drug is paclitaxel (taxol); however, in contrast to paclitaxel and most other taxanes, EpoD and selected congeners are brainā€penetrant: an essential requirement for a therapeutic candidate designed to influence axon regrowth after avulsion at the CNS/PNS transitional zone as used by Li and Wu (). Other studies have shown that brainā€penetrant microtubuleā€stabilizing drugs such as EpoD or dictyostatin reduce axonal dysfunction and improve cognition in mouse models of tauopathy (Zhang et al ., ; Makani et al ., ).…”
Section: Microtubule Stabilization: a Promising Drug Targetmentioning
confidence: 99%
“…Thus, potentially harmful side effects might limit the use of general microtubule stabilizers during longā€term treatment, as would be required for the therapy of AD or PD. The use of microtubule stabilizers as a potential treatment for acute conditions such as spinal root avulsion caused by accidents as described in the paper by Li & Wu () may have a greater chance to be of benefit for the patients.…”
Section: Meddling Around With Microtubule Dynamics: a Word Of Cautionmentioning
confidence: 99%
See 1 more Smart Citation